Stability of bioactive compounds in minimally processed beet according to the cooking methods - Ramos, Juliana Arruda; Furlaneto, Karina Aparecida; Lundgren, Giovanna Alencar; Mariano-nasser, Flávia Aparecida De Carvalho; MendonÇa, Veridiana Zocoler; Nasser, Maurício Dominguez; Vieites, Rogério Lopes (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2017)
Abstract The current study aimed to determine the functional propriety of fresh beets under different cooking methods through the quantification of bioactives compounds. Beets were chosen for uniformity of size, color and absence of defects. They were thoroughly washed in running water to remove dirt, manually peeled with a knife, sliced through a stainless-steel food processor (5 mm slicing disc) and submitted to four different cooking methods: steaming, pressure, oven-baked and hot-water immersion. Analysis were performed in both uncooked and cooked beets to evaluate antioxidant activity, total phenolic content, carotenoids, flavonoids and betalains. The experiment was completely randomized design (CRD). Data were subjected to analysis of variance (F test) and means were compared by Tukey test (p < 0.05). Oven-baked beets preserve most of the bioactive coumpouds, maintaining better levels of carotenoids, flavonoids, betacyanin and betaxanthin than the other cooking methods. The antioxidant activity was similar between the treatments, except in the pressure. Moreover, different cooking methods did not affect phenolic compounds concentration in beets.
Keywords: Beta vulgaris L.; antioxidants; betalains